Mobile device security : a comprehensive guide to securing your information in a moving world - Fried, Stephen , 1962- (Boca Raton, Florida : Taylor & Francis Group, 2010)
Explaining how mobile devices can create backdoor security threats, this title specifies immediate actions you can take to defend against these threats. Highlighting the risks inherent when mobilizing data, it supplies a proven methodology for identifying, analyzing, and evaluating these risks
1. What are you trying to protect? -- 2. It's all about the risk -- 3. The many faces of mobility -- 4. Data at rest, data in motion -- 5. Mobile data security models -- 6. Encryption -- 7. Defense-in-depth: mobile security controls -- 8. Defense-in-depth: specific technology controls -- 9. Creating a mobile security policy -- 10. Building the business case for mobile security
Includes bibliographical references and index
Keywords: Computer security; Data protection; Mobile communication systems -- Security measures